Tinjauan Fikih dan Dampak Ekonomi Jual-Beli Tawaruk - Muhammad Nabhani; Syukron (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. Many of the practices of buying and selling Tawaruk that occur in Tegalgubug require a review of fiqh and the economic impact for local communities and the perpetrators of buying and selling.Aim. This study aims to conduct a fiqh review of the practice of buying and selling Tawaruk and the economic impact.Methods. This research is a qualitative research with a literature study approach to fiqh and economic studiesResults. . The results of the practice of buying and selling Tawaruk in fiqh still contain the problem of ikhtilafiyah (forbidden, allowed, makruh) among the fuqoha, but there is a risk to usury because it is feared that the value of goods will continue to increase which is detrimental to people who owe the goods. If a fine is imposed due to late payment, it is included in usury activities. The sale and purchase of Tawaruk has a positive impact on the economic growth of local residents and buyers from outside the city.